Does gray divorce delay retirement? - Berkowicz, Sara Stolberg (Kansas State University, 2019)
Baby Boomers are the only demographic cohort whose divorce rate increased from 1990 to 2010. All other age groups experienced lower rates of both marriage and divorce. Divorce tends to reduce wealth at the time it occurs, but longer-term effects differ by gender. Divorcing after or just before retiring may have devastating financial consequences for hundreds of thousands of older adults. Baby Boomers are the largest cohort to face retirement to date. In 2018, 70 million Boomers are age 54 – 72 years old. Yet, most of them have not saved enough to sustain decades-long retirement periods. The short- and long-term economic effects of a massive drop in workforce participation and application for government-paid retirement benefits could be enormous. This study used the 2014 wave of a large, national representative dataset to look at Baby Boomers in their 60s. Multinomial logistic regression was conducted on a unique outcome variable that combined being retired or not with receiving Social Security benefits or not. A focused selection of predictor variables included demographic, marital status, and other lifecycle-related variables. The “Yes/No” gray divorce variable was merged with the variable measuring divorce recency to unify the context of economic shocks at different lifecycle stages. The regression models were run separately by gender. Gray divorce was not a significant predictor for any combination of retiring and receiving Social Security benefits. Later-life marital dissolution did not play a role in respondents’ retirement behavior. A significant effect was found for divorces that had occurred 13 – 24 years earlier, when respondents were in their 40s. The study has implications for future research, policy, and practitioners.
Keywords: Gray divorce; Retirement; Baby Boomers; Social Security; Labor economics; Divorce